1981
DOI: 10.1111/j.1440-1681.1981.tb00130.x
|View full text |Cite
|
Sign up to set email alerts
|

Adrenaline Depletion in the Hypothalamus of the Rat After Chronic Α‐methyldopa

Abstract: 1. Individual anterior hypothalamic-preoptic nuclei were dissected from the brains of control and alpha-methyldopa treated (2 x 40 mg/kg, 5 days) rats, and the concentrations of adrenaline and other catecholamines were estimated. 2. By a combination of radioenzymatic assay and paper chromatography the concentrations of adrenaline, noradrenaline, dopamine, alpha-methylnoradrenaline and alpha-methyldopamine were determined concurrently in the same sample. 3. alpha-Methyldopa reduced the adrenaline levels of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1982
1982
1991
1991

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 20 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…22 -23 At this stage the functional significance of methylepinephrine is uncertain, but this amine may be involved in the depletion of epinephrine from medullary and anterior hypothalamic nuclei seen after chronic administration of methyldopa. 24 Moreover, the work of Dampney, 23 Blessing et al, 26 and Reis et al 27 suggests that the Cl region, which is important in cardiovascular control, contains high concentrations of epinephrine. More recently Robertson et al 28 have demonstrated that administration of methylepinephrine into either the lateral ventricle or the NTS produces a prolonged antihypertensive effect.…”
Section: Methylepinephrinementioning
confidence: 99%
“…22 -23 At this stage the functional significance of methylepinephrine is uncertain, but this amine may be involved in the depletion of epinephrine from medullary and anterior hypothalamic nuclei seen after chronic administration of methyldopa. 24 Moreover, the work of Dampney, 23 Blessing et al, 26 and Reis et al 27 suggests that the Cl region, which is important in cardiovascular control, contains high concentrations of epinephrine. More recently Robertson et al 28 have demonstrated that administration of methylepinephrine into either the lateral ventricle or the NTS produces a prolonged antihypertensive effect.…”
Section: Methylepinephrinementioning
confidence: 99%
“…brain) or no PNMT activity. The concentration of a-methyladrenaline found in whole hypothalamus represented < 5% of the adrenaline concentrations found in individual hypothalamic nuclei (Beart et a1 1979), and thus a-methyladrenaline is unlikely to be responsible for the 50-70% depletion of adrenaline seen after a-methyldopa (Beart et al 1981). &-Methyladrenaline would appear to differ from a-methylnoradrenaline and a-methyldopamine in that the large accumulation of these a-methylamines is considered to be responsible for the replacement of noradrenaline and dopamine.…”
mentioning
confidence: 99%